ANALYSIS OF THE ROLE OF HUMAN RESOURCE MANAGEMENT IN IMPROVING EMPLOYEE PERFORMANCE AND ENTREPRENEURIAL INTEREST AMONG STUDENTS OF DARUL ‘ULUM ISLAMIC UNIVERSITY OF LAMONGAN - Rahardini, Trivana; Martha Laila Arisandra (Az-Zahra Media Society, 2025)
Human Resource Management has a crucial role in improving employee performance and entrepreneurial interest among students, especially at Darul Ulum Islamic University Lamongan. In the midst of the era of globalization, the implementation of efficient HRM can help organizations achieve higher productivity through appropriate policies and practices. This study adopts a quantitative approach by conducting hypothesis testing. Quantitative research methods are scientific methods because they meet scientific standards such as concrete/empirical, objective, measurable, rational, and systematic. This method is called quantitative because the research data is in the form of numbers and analysis using statistics. Entrepreneurial motivation has a positive and significant influence on entrepreneurial interest among students in Lamongan Regency. The results of this study indicate conformity with the partial significance test (t-test) which shows that the Entrepreneurial Motivation variable (X1) has a t-value of 2.345> 1.96 and the significance value produced in the t-test is 0.019 <0.05, so it can be concluded that H1 is accepted. This means that the increasing or stronger the motivation to become an entrepreneur that is conveyed, the greater the interest of students in Lamongan Regency to become entrepreneurs. The results of this study are expected to be a motivation and guideline for subsequent researchers, so that they can develop this research, either by using other variables that have the potential to influence Entrepreneurial Interest or by choosing more detailed research objects.